Higher accuracy with fewer projections? Automated scan angle selection for dimensional Computed Tomography based on a simple data completeness measure for the part surface - Butzhammer, Lorenz; Braun, Matthias Robert Oskar; Herath, Colin; Hausotte, Tino (e-Journal of Nondestructive Testing)
Selecting scan angles such that surface segments are aligned with straight X-ray paths (i.e., rays are tangential to the surface and therefore perpendicular to the local surface normal) is known to produce sharper transitions of those surface segments in the reconstructed volume. This enhances dimensional accuracy in sparse-view computed tomography (CT). However, existing approaches offer no direct means to exploit this criterion for automatic scan-angle optimization. We propose a method that uses a virtual representation of the CT setup, including an STL surface model of the inspected part, to automatically identify taskspecific scan angles. Using elementary vector calculus, the algorithm determines projection directions that generate tangential X-rays for targeted surface segments. To support different levels of geometric complexity, we introduce two variants of the angle-selection procedure. The methods were experimentally validated on two objects with distinct absorption and geometric characteristics. For a steel gauge block, employing the minimum number of task-specific projections required for surface-data completeness substantially outperformed a conventional high-projection scan. For a geometrically more complex test object, surface-related errors were still reduced within the region of interest. The proposed approach – particularly suited for flat surface structures and not accounting for image-degrading factors other than cone-beam artifacts – shows promise for high-throughput dimensional metrology of mono-material parts.

Conversion between detector- and rotary-table-related misalignment parameterisations for unified projection-matrix-based geometry calibration in dimensional X-ray computed tomography - Butzhammer, Lorenz (Precision Engineering)

Direct assessment of the influence of pose repeatability on the accuracy of dimensional measurements for computed tomography systems with high degrees of freedom - Butzhammer, Lorenz; Handke, Niklas; Wittl, Simon; Herl, Gabriel; Hausotte, Tino (Measurement Science and Technology)
Abstract Industrial x-ray computed tomography (CT) systems with high geometric flexibility are increasingly utilized for large-scale measurement objects or challenging measurement tasks. To maintain high accuracy when deviating from the established circular scan trajectory, trajectory calibration methods using multi-sphere reference objects with known marker positions are commonly employed. These multi-sphere objects can either be scanned together with the measurement object (online trajectory calibration) or in a separate scan (offline trajectory calibration). While offline calibration increases machine time, it generally results in higher scan quality. However, a sufficient pose repeatability is necessary to ensure comparable or even superior accuracy to online calibration. In this contribution, we present a straightforward procedure to compare both types of trajectory calibration in a way that the differences of the results can directly be traced back to the influence of the pose repeatability. The multi-sphere reference object is not only used for trajectory calibration, but simultaneously as a measurement object for repeated measurements. The methodology is tested on both a twin robotic CT system and a conventional CT system that is additionally equipped with a hexapod manipulator for adaptive object tilting. Results showed, independent from the type of trajectory calibration, systematic measurement errors in the order of 10 −5 –10 −4 of measured sphere distances and sphericity values below 50 μ m . For sphere distances, random errors were increased by a factor of 5 due to the offline trajectory calibration, but were still low ( < 1 μ m ) in comparison to systematic errors and the spread of different measurement features. Overall, both investigated systems demonstrated sufficient positioning repeatability for offline trajectory calibration. The method is in general also applicable to any other types of manipulator systems used for CT devices. It provides a workflow for the decision which type of trajectory calibration is preferable for a given CT system.

Modifizierter Torsionsversuch zur Untersuchung des Tragverhaltens von Clinchpunktmehrfachanordnungen - Lüder, Stephan; Wolf, Eugen; Brosius, Alexander; Schmale, Hans Christian (43. Vortrags- und Diskussionstagung Werkstoffprüfung 2025)
Zur Prüfung der mechanischen Eigenschaften von mechanisch gefügten Verbindungen wird gemäß der Normung in der Regel nur ein Fügepunkt verwendet. In diesem Beitrag wird die Prüfung von Mehrfachanordnungen von Clinchpunkten in einem modifizierten Torsionsversuch beschrieben. Bei den Fügeverbindungen der Proben aus artgleichen Werkstoffen handelt es sich um zwei Varianten symmetrischer Mehrfachanordnungen von vier Clinchpunkten mit zwei unterschiedlichen Fügepunktabständen, was zu zwei verschiedenen Längen des Wirkabstands in Bezug auf die Rotationsachse im Torsionsversuch führt. Das erste Teilziel der Untersuchung ist die Bewertung der Tragfähigkeit der Mehrfachanordnungen von Clinchpunkten unter Torsionsbeanspruchung. Ein zweites Teilziel ist die Analyse des Einflusses eines zusätzlichen Clinchpunkts, der als Drehgelenk in der Rotationsachse wirkt, auf das Tragverhalten und das Versagensverhalten der Fügeverbindung. Aus den erarbeiteten Resultaten werden Erkenntnisse zum Tragverhalten der Fügeverbindungen abgeleitet und eine Überschlagsrechnung vorgestellt, um Richtlinien zur konstruktiven Auslegung von Bauteilen aufzustellen.
Keywords: Clinchen; Mehrfachanordnung; Torsionsprüfung; Tragfähigkeit

Untersuchung der Zuverlässigkeit gefügter Proben mit einer Mehrfachanordnung von Clinchpunkten unter zyklischer Beanspruchung - Wolf, Eugen; Hollmer, Katharina; Zimmermann, Martina; Brosius, Alexander (43. Vortrags- und Diskussionstagung Werkstoffprüfung 2025)
Durch eine zunehmende Verbreitung von Clinchverbindungen in industriellen Anwendungen spielt die Zuverlässigkeit der Fügeverbindung eine immer größere Rolle. Insbesondere Mehrfachanordnungen von Clinchpunkten wurden bisher nur selten untersucht. In der vorliegenden Arbeit wird die Zuverlässigkeit von gefügten Proben mit einer Mehrfachanordnung von Clinchpunkten unter zyklischer Beanspruchung untersucht. Ziel ist es, die Wechselwirkung benachbarter Clinchpunkte und deren Einfluss auf die Ermüdungslebensdauer zu untersuchen. Dazu wurden Proben mit variierenden Fügepunktabständen hergestellt und in Versuchsreihen zyklisch belastet. Die Resultate zeigen, dass die räumliche Anordnung der Clinchpunkte das Ermüdungsverhalten beeinflusst. Es wurde festgestellt, dass bei Mehrfachanordnungen sowohl der Fügepunktabstand als auch der Abstand der Fügepunkte zum Bauteilrand in Belastungsrichtung einen Einflussfaktor darstellen. Die vorliegende Arbeit leistet somit einen Beitrag zur Lebensdauervorhersage gefügter Strukturen und bildet eine Grundlage für weiterführende Untersuchungen zu Gestaltungsempfehlungen.
Keywords: Clinchverbindungen; Zyklische Beanspruchung; Versagensverhalten

Investigation failure behavior in the shear tensile test with variety of specimen stiffness - Wolf, Eugen; Brosius, Alexander (MATEC Web of Conferences)
This paper focuses on the failure behavior of clinched specimens with various stiffnesses under shear tensile loading. The primary objective is to assess the influence of the specimen stiffness with an arrangement of clinched joints. The specimen stiffness depends on several variables. In addition to the material selection, the specific choice of geometry and the design of the clinched joints must also be taken into account. A number of experiments was conducted to investigate the failure behavior of specimens with an arrangement of three clinched joints under shear tensile loading. These configurations were subjected to shear tensile tests, with force displacement curves recorded for each specimen to provide a detailed characterization of their structural response. The stiffness is modified by altering the specimen width, which has marginal impact on the maximum force. The experimental findings indicate that reducing the specimen stiffness results in a shift in the type of stress, with the failure behavior becoming increasingly influenced by bending stress. These results offer important insights for the design of clinched joint assemblies, indicating that it is feasible to achieve the desired properties by changing the specimen stiffness.
Keywords: Joining; Sheet Metal; Stiffness; Clinching

Investigation failure behavior in the shear tensile test with respect to the arrangements of clinched joints - Wolf, Eugen; Brosius, Alexander (Materials Research Proceedings)
This paper focuses on the failure behavior of specimens with various configurations of clinched joints under shear tensile loading. The primary objective is to assess the influence of the joining direction and the spatial arrangement of clinched joints on their mechanical performance. A number of experiments was conducted, focusing on three clinched joints arranged in different configurations, each varying in terms of joining direction and spacing. These configurations were subjected to shear tensile tests, with force-displacement curves recorded for each sample to provide a detailed characterization of their structural response. The experimental findings indicate that the specific arrangement of the clinched joints, in terms of joining direction, has a marginal impact on the overall failure behavior. This suggests that intricate modifications to the joining direction are unnecessary to achieve improved mechanical performance in such applications. These results offer valuable insights for the design of clinched joint assemblies, indicating that simplified joining strategies may suffice without compromising structural integrity under shear loading.
Keywords: Joining; Sheet Metal; Clinching

A new joint with versatile properties based on a Reuleaux triangle geometry - Steinfelder, Christian; Acksteiner, Clemens; Brosius, Alexander (CIRP Annals)
Non-rotationally symmetrical joints can have different properties that can be controlled by the joint orientation. This hypothesis is tested using a Reuleaux triangle joint geometry. A tool design is carried out, followed by a numerical sensitivity analysis of the tool geometry. Initial tools were manufactured for experimental investigations and then adapted based on the findings of the sensitivity analysis. The joints are characterized by micrographs, 3D scans, shear tensile tests, head tensile tests and three-point bending tests and compared with a round geometry. The analysis confirms the hypothesis. Thus, joints with adaptable properties can be produced with one tool set.
Keywords: Joining; Forming; Property adjustment

Analysis of the binding mechanisms depending on versatile process variants of self-piercing riveting - Lüder, Stephan; Holtkamp, Pia Katharina; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson; Lechner, Michael; Schmale, Hans Christian (Materials Research Proceedings)
The constantly increasing demand for climate protection and resource conservation requires innovative and versatile joining processes that improve adaptability to the joining task and robustness to enable flexible manufacturing on a production line. Therefore, the versatile SPR (V-SPR) and tumbling SPR (T-SPR) were developed. Using the example of a mixed material combination HCT590X+Z (t0 = 1.0 mm) / EN AW-6014 T4 (t0 = 2.0 mm), these processes were examined and compared with regard to the binding mechanisms form closure and force closure using micrographs, non-destructive resistance measurements and destructive torsion tests. For this purpose, a new sample geometry was defined, and the methods were adapted to the SPR process variants.
Keywords: Joining; Self-Piercing Riveting; Sheet Metal

Investigation of the impact of a rotationally superimposed punch stroke on the binding mechanisms of a clinched joint - Lüder, Stephan; Wolf, Eugen; Schmale, Hans Christian; Brosius, Alexander (MATEC Web of Conferences)
This paper examines the impact of a rotationally superimposed punch stroke on the binding mechanisms of clinched joints of aluminum sheets. As part of the development of a method for ensuring the versatility of clinching, an additional rotational movement of the punch was introduced as a control variable to influence friction in the mechanical joining process. The effect of rotational superimposition on the force-displacement curve of the clinching processes was investigated using four test variants with different kinematics. The primary objective was to evaluate the binding mechanisms that maintain the integrity of the clinched joint. To evaluate the force closure of the resulting joint, two testing methods were employed throughout the course of the research, non-destructive resistance measurement using four-wire sensing method and destructive torsion testing. A crucial factor influencing the efficacy of the process is surface cleanliness, as contaminants between joining partners can impede the effectiveness of the clinched joint. Therefore, all specimens were meticulously cleaned prior to experimentation. This method exhibits promising potential in creating clinched joints that align with the demands of flexible manufacturing environments.
Keywords: Joining; Sheet Metal; Tribology; Clinching

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Influence of process variations on clinch joint characteristics considering the effect of the nominal tool design - Zirngibl, C; Goetz, S; Wartzack, S (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Focusing on upcoming challenges in lightweight design, such as increasing emission targets or novel multimaterial connections, versatile applicable and environmentally friendly production technologies are crucial. In this context, mechanical joining technology clinching offers a fast and energy-efficient procedure for assembling sheet metals, being a proper alternative to established joining methods, such as spot welding. However, the design of clinch points is a challenge, which is partly supported by numerical or data-based approaches for optimal tool dimensions assuring proper joint characteristics. While this is usually done for an ideal environment, real joining processes are characterized by multiple inevitably varying parameters, e.g. of the material, which have a significant impact on the quality of clinch points. Therefore, this contribution addresses the current gap by analyzing the effect of parameter variations or uncertainties on the resulting joint characteristics and studying the impact of the nominal tool design. Thus, an efficient meta-model-based variation simulation procedure is proposed and used for analyzing the effect of different tool design configurations and variation scenarios. Based on the results, it was found that varying process parameters have a strong impact on the resulting joint characteristics, whereby the effect significantly depends on the nominal tool design. This reveals the potential for a robust tool design and implies that the nominal tool design and the tolerancing of parameters should be done simultaneously for a reliable virtual joining point design without extensive iterations and physical tests.

Task-specific scan trajectory modification for dimensional X-ray computed Tomography with high throughput - Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)

Influence of the material properties on the clinching process and the resulting load-bearing capacity of the joint - Steinfelder, Christian; Rempel, Dennis; Brosius, Alexander (Journal of Advanced Joining Processes)
This study focuses on the phenomenological change in material strength caused by a specific heat treatment and the subsequent analysis of the influence on the clinching process and the resulting joint properties. For this purpose, three series of tests were performed. In the first series of tests, the influence of heat treatment up to 340 °C on the mechanical properties of an age-hardenable AlMgSi alloy was investigated. Holding time and temperature were varied and the material strength was evaluated by tensile and hardness tests. Two strength-increasing and two strength-reducing heat treatment parameters were identified. In the second series of tests, selected heat treatment parameters were applied to a larger number of specimens and the joint strength was investigated by shear and head tensile tests. In the shear tensile test, mainly the properties of the punch-side material have an influence on the resulting joint strength. A change in strength of the die-side material can be neglected. In contrast, the properties of both sheets are important in the head tensile test. The strength of the joint will only increase if the strength of both sheets is increased. In general, a strength increasing heat treatment resulted in higher joint strength. In the third series of tests, the factor of punch displacement was considered, which was demonstrated to directly influence the formation of the clinched joint geometry.
Keywords: Joining by forming; Clinching; EN AW-6014; Heat treatment; Load-bearing capacity

Prozessüberwachte Eigenschaftseinstellung beim Clinchen der ausscheidungshärtbaren Aluminiumlegierung EN AW-6014 - Lüder, Stephan; Kalich, Jan; Oesterle, Hannes; Schmale, Hans Christian (Tagung Werkstoffprüfung 2024: Werkstoffe und Bauteile auf dem Prüfstand, Prüftechnik – Kennwertermittlung – Schadensvermeidung)
Die Wandlungsfähigkeit einer Prozesskette erfordert Fügeverbindungen mit gezielt einstellbaren mechanischen, elektrischen, thermischen oder chemischen Eigenschaften. Dieser Beitrag beschreibt die Untersuchungen, inwiefern beim Clinchen zweier Bleche aus der ausscheidungshärtbaren Aluminiumlegierung EN AW-6014 bereits auf Basis der Prozessüberwachung des Kraft-Weg-Verlaufs bzw. des sich daraus ergebenden Energieeintrags auf die mechanischen und elektrischen Eigenschaften der Fügeverbindung geschlossen werden kann. An einer ausgewählten Fügeaufgabe werden im Stufenversuch die gegenseitigen Abhängigkeiten der einzelnen Einflussgrößen sowie des Wärmebehandlungszustands aufgezeigt. Dabei wird zwischen den Bindemechanismen Formschluss und Kraftschluss unterschieden. Die Formschlusskomponente wird anhand der geometrischen Kenngrößen wie Bodendicke, Halsdicke und Hinterschnitt in Mikroskopieuntersuchungen an Schliffbildern und den mechanischen Eigenschaften der Fügeverbindung untersucht, die im Scherzug- und Kopfzugversuch bestimmt werden. Dazu erfolgt zudem die Charakterisierung der Versagensbilder. Zur Quantifizierung der Kraftschlusskomponente der Fügeverbindung werden das Losbrechmoment im Torsionsversuch und der elektrische Widerstand mittels Vier-Leiter-Methode ermittelt und korreliert.
Keywords: Clinchen; Aluminium; Stufensetzversuch; Bindemechanismus; Formschluss; Kraftschluss; Zugversuch; Torsionsversuch; Widerstandsmessung

Bruchmechanische Untersuchung des Dualphasenstahls HCT590X unter Temperatureinfluss - Weiß, Deborah; Duffe, Tobias; Buczek, Moritz; Kullmer, Gunter; Schramm, Britta

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems)
Abstract. The miniaturisation of components leads to new demands on measurement systems. One of these is the resolution. As a volumetric analysis method and method of non-destructive testing, industrial X-ray computed tomography (XCT) has the ability to measure geometrical features and their corresponding dimensions without destroying them and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified. In particular, the interface structural resolution, the detectability of two surfaces facing each other after surface segmentation, faces a lack of a test specimen, a corresponding measurand and a reliable method. Simulation-based XCT investigations of a method to determine this type of resolution are presented in this article using the geometry of a test specimen that contains several radially arranged holes of the same size. The borehole diameters correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. It is shown that the geometrical detectability of the test specimen surface and interface can be extended by a reasonable choice of the threshold value for surface segmentation within a defined interval. With regard to the resolving capability, a distinction is made between assured detectability and possible detectability, as well as the threshold value used when using the ISO50 threshold for surface segmentation and measurement chain completion.
Keywords: Electrical and Electronic Engineering; Instrumentation

Anrisserkennung an geclinchten Proben während einer zyklischen Belastung unter Nutzung eines Scanning Laser Doppler Vibrometers - Brosius, Alexander; Ewenz, Lars; Stephan, Richard; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Ableitung flacher Probengeometrien zur Abbildung mehraxialer Spannungszustände in Clinchverbindungen unter zyklischer Beanspruchung - Ewenz, Lars; Kuczyk, Martin; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Untersuchungen zum Geometrie- und Frequenzeinfluss bei der Ermittlung zyklischer Kennwerte geclinchter Überlappverbindungen - Ewenz, Lars; Kühne, R.; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)